2016
DOI: 10.1210/jc.2016-1990
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an AR Mutation-Negative Class of Androgen Insensitivity by Determining Endogenous AR Activity

Abstract: Context:Only approximately 85% of patients with a clinical diagnosis complete androgen insensitivity syndrome and less than 30% with partial androgen insensitivity syndrome can be explained by inactivating mutations in the androgen receptor (AR) gene.Objective:The objective of the study was to clarify this discrepancy by in vitro determination of AR transcriptional activity in individuals with disorders of sex development (DSD) and male controls.Design:Quantification of DHT-dependent transcriptional induction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 35 publications
3
43
0
1
Order By: Relevance
“…In men and women with partial AIS (PAIS), the phenotype is highly variable, depending on the degree of residual androgen activity and other modifying factors [1]. Whereas a likely pathogenic variant in AR can be identified in 85% of women who have CAIS, this is only the case in less than 30% of individuals who have clinical features suggestive of PAIS, suggesting that other mechanisms affect androgen signalling [2]. Providing care for individuals with AIS is best performed in a multidisciplinary setting and may be challenging [3-6].…”
Section: Introductionmentioning
confidence: 99%
“…In men and women with partial AIS (PAIS), the phenotype is highly variable, depending on the degree of residual androgen activity and other modifying factors [1]. Whereas a likely pathogenic variant in AR can be identified in 85% of women who have CAIS, this is only the case in less than 30% of individuals who have clinical features suggestive of PAIS, suggesting that other mechanisms affect androgen signalling [2]. Providing care for individuals with AIS is best performed in a multidisciplinary setting and may be challenging [3-6].…”
Section: Introductionmentioning
confidence: 99%
“…A firm diagnosis of AIS requires the confirmation of a mutation in the androgen receptor gene (AR). However, recent studies suggest that the molecular genetic abnormality in AR may not necessarily reside in the conventional coding region within the gene (38). Whilst there is a school of thought that molecular genetic investigations can be performed in parallel with biochemical evaluation, the current study suggests that the utility of conventional biochemical investigations such as the hCG stimulation test, itself, can include a molecular genetic component that aids the diagnosis of androgen deficiency and perhaps, androgen resistance.…”
Section: Figurementioning
confidence: 87%
“…Although androgen-responsive circulating proteins such as SHBG have been measured previously (6), this test has not been considered to be sufficiently reliable to become common practice. More recently, another androgenresponsive protein in the genital skin fibroblasts has been reported to have a greater discriminant value for androgen sensitivity (38). Genital skin fibroblast studies have also previously reported an androgen-dependent transcriptome, which could differentiate between people with and without androgen sensitivity (3).…”
Section: Figurementioning
confidence: 95%
“…An example is the assay that uses DHT-dependent transcriptional induction of the androgen receptor (AR) target gene apolipoprotein D in genital skin fibroblasts to assess androgen action [Hornig et al, 2016]. This assay is able to discriminate between individuals with androgen insensitivity caused by an AR mutation and unaffected individuals.…”
Section: Novel Testsmentioning
confidence: 99%